Frozen : the songs [compact disc] - Anderson-Lopez, Kristen; Lopez, Robert, 1975-; Bell, Kristen, 1980-; Groff, Jonathan; Menzel, Idina; Monn, Agatha Lee, 2003-; Lopez, Katie; Fontana, Santino; Wilson, Maia Nkenge; Lovato, Demi, 1992-; Gad, Josh, 1981- (Walt Disney Records, 2014)
One of the biggest animated films of all time delivers a new collection featuring ten of its most popular songs, including the Academy Award-winning Let It Go as well as Do You Want to Build a Snowman.